Characterization of a k-Carrageenase-producing marine bacterium, isolate ALAB-001 - Tayco, Crimson C.; Tablizo, Francis A.; Regalia, Raymond S.; Lluisma, Arturo O. (2013)
Carrageenases are glycoside hydrolases that specifically degrade carrageenan, a highly anionic polysaccharide found in the cell wall of many red algal species. To date, only a few of these enzymes have been characterized, and identifying additional sources is important considering the role of carrageenases in production of carrageenan derivatives. In this paper, we report the characterization of a marine bacterial strain that produces κ-carrageenase. The strain, which we designate as ALAB-001, was isolated from diseased thallus fragments of the red alga Kappaphycus alvarezii, a commercially important source of carrageenan. Genotypic and phenotypic data suggest that the isolate belongs to a relatively poorly-characterized group of bacteria in Alteromonadaceae (Alteromonadales) and is closely related to Marinimicrobium and Microbulbifer. Significant κ-carrageenase activity (175 U/mL) was evident when the isolate was grown in the presence of κ-carrageenan. Activity against starch was also high (180 U/mL), but activity against agar, alginate, cellulose, ι-carrageenan, and λ-carrageenan was significantly lower (25-50 U/mL). Laboratory-scale production of the enzyme using batch cultures of the isolate was achieved by optimizing culture medium, length of culture time and degree temperature. Optimal growth was observed at 25°C, though the isolate survived at 30°C. An in-house developed seawater-based medium containing equal concentrations of yeast extract and tryptone (YETS) yielded the highest cell growth based on total protein concentration (~ 3000 μg/mL) and enzyme activity (~ 45 U/mL).
Keywords: Marine bacteria; Carrageenans